IFRS and the value relevance of earnings: evidence from the emerging market of Romania. (16th February 2010) - Filip, Andrei
This paper investigates the impact of the mandatory IFRS adoption on the value relevance of earnings on the Bucharest Stock Exchange, at a time when the EU did not have an official position regarding IFRS. Findings suggest that the implementation of IFRS has increased the contemporaneous association between market returns and earnings. Additional analyses reveal that this result is mainly driven by small firms and that the accounting reforms have increased the timeliness of earnings. In the light of the expansion of IFRS worldwide, this paper examines the mandatory IFRS adoption in an institutional setting where accounting reforms were accompanied by economic reforms in preparation for Romania's accession to the EU. Such a single-country case study may help researchers better understand the impact of accounting regulations and institutional factors on the properties of accounting earnings.